Megrelian Vocabulary According to Sulkhan-Saba's "Sitkvis kona" - Gejua, Keso (Actual Problems of Kartvelology, 2019)
Many scientists still work on the detection of Megrelian-Laz units recorded in Sulkhan-Saba Orbeliani's "Sitkvis kona" (I. Kipshidze (1914), Iv. Javakhishvili (1937), M. Alavidze (1959), K. Danelia (1991)), T. Bolkvadze (2005), R. Sherozia (2007,2015), E. Dadiani (2009)). During the development of the dictionary, in addition to the units previously analyzed by researchers, word forms of Megrelian origin were also found. The article analyzes the units of order, [ganligeba], [gurioba], [dačinčeba], [ḳolomani], [narin], [saudeli], [peliḳi].